Evaluating Factors that Contribute to the Early Loss of Bone Around Submerged Implants Before they are Restored - Fazil Arshad Nasyam; Mohammed Anas Kadri; Sumit Singh; Vikash Pandey; Tanu Sahney; Kanika Kaushik; Pratik Surana (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of the present study was to examine various factors that may contribute to early crestal bone loss around submerged implants, prior to restoration. Methods: The research included a collective of 100 implants, procured from 60 participants. We allocated a total of 60 patients into two distinct groups: 20 individuals in the healthy group and 40 individuals in the ECBL group. Results: Out of the complete population, 56 people were unaffected by diabetes, while six persons were smokers. Systemic antibiotics were administered to almost all patients (98%) throughout the implantation procedure. The implant implantation consisted of 69% nonmolar implants and 31% molar implants. Conclusion: Engaging in a guided bone regeneration (GBR) operation before implant implantation has been shown to be a statistically significant factor in preventing early crestal bone loss (ECBL).